Global labour markets and workplaces in the age of intelligent machines - Aleksandr Ključnikov; Elena G. Popkova; Bruno S. Sergi (Journal of Innovation & Knowledge (JIK), 2023)
This paper examines how labour productivity will increase in future workplaces that employ human resources and machine technologies. This paper expands the concept of intelligent machines as systems of automating labour based on robots and artificial intelligence. Furthermore, it aims to develop recommendations for improving productivity by managing competition and marketing in current global labour markets. We model the dependence of output per worker on robots' international distribution, the ease of hiring foreign labour, and the dependence on pay and productivity. As a result of this research, labour productivity is defined by human resource availability and not through automation. The study develops comprehensive guidance for economic policy in the global labour market for the medium-term period. Management implications include representing a vision for the future of workplaces drawn on the productivity benefits of different workplace models that stimulate growth in labour efficiency. The recommended concept validates how innovation and digitalisation reshape the workplace.
Keywords: 650; Manufacturing innovation; Industrial innovation; Inclusive innovation; Intelligent machines; Human resources; Labour productivity; Future workplaces; Technology